Classification of interior noise comfort level of Proton model cars using artificial neural network - Andrew, Allan Melvin (School of Mechatronic Engineering, 2012)
In this research, a proton model cars noise comfort level classification system has been developed to detect the noise comfort level in cars using artificial neural network. This research focuses on developing a database consisting of car sound samples measured from different proton make cars in stationary and moving state.